2007
DOI: 10.3844/ajassp.2007.768.773
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Properties and Compressibility Behavior of Tropical Peat Soil

Abstract: This paper presents the engineering properties and compressibility behavior of various types of tropical peat soil collected from several locations in Malaysia. These soils represented fibric, hemic and sapric type of tropical peat with organic content ranging from 70% to 90%. The correlations of the various basic engineering properties of the tropical peat soils have been found to be close and new equations have been established. Loss on ignition (Organic Content) appears to be a very useful parameter for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 4 publications
2
26
2
1
Order By: Relevance
“…As mentioned previously, many of the tall buildings, including the Q1 tower are located in the centre of the study area within these two cross sections. Moreover, physical and engineering properties of the peat layer have been obtained from the soil investigation reports of the Surfers Paradise area Table 2. the literature (Huat 2004;Duraisamy et al 2007;Huat et al 2009) and showed that the peat in Surfers Paradise falls within the range of the tropical peat. The …”
Section: Resultsmentioning
confidence: 99%
“…As mentioned previously, many of the tall buildings, including the Q1 tower are located in the centre of the study area within these two cross sections. Moreover, physical and engineering properties of the peat layer have been obtained from the soil investigation reports of the Surfers Paradise area Table 2. the literature (Huat 2004;Duraisamy et al 2007;Huat et al 2009) and showed that the peat in Surfers Paradise falls within the range of the tropical peat. The …”
Section: Resultsmentioning
confidence: 99%
“…In this research, the tube sampler taken from the site was carefully extruded and cautiously trimmed to a diameter of 50mm and a height of 100mm using a sharp knife and was quickly weighted to minimize the disturbance on the moisture content [14]. For triaxial testing, the specimen was enclosed in a high-density latex membrane and porous stones and filter papers were inserted at the ends of the specimen.…”
Section: Test Materials and Methods Approachmentioning
confidence: 99%
“…The binder is carried in pressurized tanks, which are mounted on the rig itself or on a separate shuttle. A research has been carried out in University Putra Malaysia (UPM) to examine the effect of cement column on the compressibility of peat soil [7] . When a cement column is installed in peat, its compressibility is reduced because of the hardened skeleton matrix formed by cement particles bonding with adjacent soil particles in the presence of pore water.…”
Section: Various Construction Methods For Peat Excavation -Displacemementioning
confidence: 99%
“…The results indicated that compressibility index Cc and Cα decreased with increasing diameter of the cement column. Specimens with 45 mm and 60 mm diameter of cement columns were cured for 28 days, after which they were subjected to Rowe Cell Consolidation test [7] . Undisturbed samples of peat soil were taken from three different locations in Banting (located on the West coast of Peninsular Malaysia) by using a sampling tube.…”
Section: Various Construction Methods For Peat Excavation -Displacemementioning
confidence: 99%